G176(P) Healthcare utilisation in SMA type 1 patients treated with nusinersen. (May 2019) - Ali, I; Gilchrist, F; Carroll, WD; Alexander, J; Clayton, S; Willis, T; Samuels, M
Abstract : Background: Spinal muscular atrophy (SMA) Type 1 is a neuromuscular disorder that has traditionally resulted in death from respiratory failure before 2 years of age. Treatment with Nusinersen, an antisense oligonucleotide has the potential to transform the prognosis for these children, offering hope of treatment for the first time. It has been used in the UK since early 2017, costing £4 50 000 in the first year and £2 25 000 per annum subsequently. However, as with all new treatments, its longer term effectiveness is unknown and the treatment burden for families and health economies is yet to be established. Aims: To establish the hospital utilisation and associated costs for children treated with Nusinersen. Methods: We reviewed the medical records of all children with SMA1 in the West Midlands who received Nusinersen. As well as collating baseline patient demographics, we collected information on all hospital admissions including reason for admission; number of days on the ward, HDU, PICU and intubated; diagnosis at discharge; number of Nusinersen doses and complications following its administration. Results: Nine children (six girls) had received Nusinersen since June 2017. They had a median (range) age of 22 (9–89) months. The median (range) number of Nusinersen doses was 5 (4–6). Seven children receive BiPAP and one child is ventilated via tracheostomy. The total number of days in hospital since diagnosis was 665 with median (range) hospital days of 64 (4–177) days. This included HDU 52 (4–116) days and PICU 4 (0–103) days. This equates to each child spending a mean of 32% of their life on HDU/PICU. Three spent ≤2% of their life in hospital, three 30%–60% and three>60%. Conclusion: Patients with SMA1 treated with Nusinersen are likely to spend at least a third of their early life in hospital and parents should be counselled accordingly. Treatment with Nusinersen is costly, not only because of the cost of the drug, but because of significant health care utilisation, including time spent receiving critical care.